Critical size defect model on the femur in rabbits - Crigel, M.-H.; Balligand, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
The study purposed to elaborate a model of non-union to test a new biomaterial enhancing bone healing in large segmental defects. The authors’ concern was to develop a model of osteosynthesis capable of maintaining the stability of a femur that sustained a segmental defect. Also, they intended to determine the length of a defect that would create a nonunion. The madel was a 20-mm segmental bone defect coupled with an appropriate osteosynthesis in the rabbit femur. Two groups of rabbits underwent a mid-shaft ostectomy. Osteosynthesis was mode by two superposed holes 2-mm cuttable plates with cerclage wires. In one group, an additional intramedullary pin was inserted. The experiment lasted 16 weeks. The rabbits of the control group suffered fracture of the plates before the end of the experiment. The rabbits of the test group showed stability of the implants and nonunion of the defect. It was concluded that a mid-shaft segmental defect of 20 mm, coupled with an osteosynthesis combining plates, wires and intramedullary pin, is a valid critical size defect model in the rabbit femur.
Keywords: Rabbit; bone; segmental; critical size defect